1989
DOI: 10.1172/jci114339
|View full text |Cite
|
Sign up to set email alerts
|

Insulin transport across capillaries is rate limiting for insulin action in dogs.

Abstract: This study examined the relationship between transcapillary insulin-transport and insulin action in vivo. During euglycemic clamps (n = 7) in normal conscious dogs we simultaneously measured plasma and thoracic duct lymph insulin and glucose utilization (Rd). Clamps consisted of an activation phase with constant insulin infusion (0.6 mU/kg per min) and a deactivation phase. 14CIInulin was infused as a passively transported control substance. While [14Cjinulin reached an equilibrium between plasma and lymph, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
237
3
3

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(263 citation statements)
references
References 52 publications
20
237
3
3
Order By: Relevance
“…In dogs the rate of glucose utilisation correlates better with changes in lymph insulin (thought to be representative of interstitial insulin) than with changes in plasma insulin concentration [42]. In this and our previous study [43] we found a slower increase in clamp glucose requirement in cirrhotic patients.…”
Section: Discussionsupporting
confidence: 60%
“…In dogs the rate of glucose utilisation correlates better with changes in lymph insulin (thought to be representative of interstitial insulin) than with changes in plasma insulin concentration [42]. In this and our previous study [43] we found a slower increase in clamp glucose requirement in cirrhotic patients.…”
Section: Discussionsupporting
confidence: 60%
“…Studies in lymph [35] as well as in interstitial fluid [10] by means of microdialysis have shown that the interstitial insulin concentration is about 50 % lower than in arterial plasma. In rat muscle, however, a clear difference between interstitial muscle insulin and plasma insulin is evident only at concentrations in the upper physiological range, that is beyond approximately 1.5 nmol/l, which in our clamp model equals the EC 50 for the effect of insulin on glucose infusion rate [36].…”
Section: Discussionmentioning
confidence: 99%
“…The transendothelial insulin transport is an important regulator of the interstitial insulin concentration, which is normally lower than in plasma [33]. Changes in blood flow may thus affect the amount of insulin delivered to the interstitial fluid [34]. However, changes in endothelial binding capacity of insulin during haemodynamic changes may affect the plasma insulin level without altering the interstitial insulin concentration [35].…”
Section: Discussionmentioning
confidence: 99%
“…Post-treatment analyses confirmed that noradrenaline as well as adrenaline levels increased significantly with metoprolol treatment [38], whereas no changes were seen in testosterone or cortisol levels. Regarding the importance of the capillary surface area for insulin distribution [34], it may be speculated that an increase in a-adrenergic activity as a result of increased catecholamine levels during b-adrenergic blocking treatment may be an underlying mechanism for the change in insulin levels during an insulin clamp. Interestingly, it was recently demonstrated in our laboratory that an adrenaline infusion during insulin clamp in rat resulted in increased plasma concentrations of insulin, without changes in the muscle interstitial insulin concentration (unpublished data).…”
Section: Discussionmentioning
confidence: 99%